2022
DOI: 10.1038/s41598-022-16062-0
|View full text |Cite
|
Sign up to set email alerts
|

Applying machine learning and predictive modeling to retention and viral suppression in South African HIV treatment cohorts

Abstract: HIV treatment programs face challenges in identifying patients at risk for loss-to-follow-up and uncontrolled viremia. We applied predictive machine learning algorithms to anonymised, patient-level HIV programmatic data from two districts in South Africa, 2016–2018. We developed patient risk scores for two outcomes: (1) visit attendance ≤ 28 days of the next scheduled clinic visit and (2) suppression of the next HIV viral load (VL). Demographic, clinical, behavioral and laboratory data were investigated in mul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“… 33 , 36 , 44 This is somewhat higher than Maskew et al, which reports that ML based predictive modeling achieves an AUC of 0.76. 39 Recently, Kamal et al conducted a study employing RF-based prediction of virologic outcomes in Switzerland, which achieved an AUC of 0.77. 38 Meanwhile, our accuracy finding is in agreement with a study of Bisaso et al, which reports a predictive modeling accuracy of 92.9%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 33 , 36 , 44 This is somewhat higher than Maskew et al, which reports that ML based predictive modeling achieves an AUC of 0.76. 39 Recently, Kamal et al conducted a study employing RF-based prediction of virologic outcomes in Switzerland, which achieved an AUC of 0.77. 38 Meanwhile, our accuracy finding is in agreement with a study of Bisaso et al, which reports a predictive modeling accuracy of 92.9%.…”
Section: Discussionmentioning
confidence: 99%
“… 38 , 39 , 52 Furthermore, duration on ART was an important feature for predicting virological failure. Participants who had a longer duration of stay on ART had a higher risk of developing virological failure; this is consistent with the previous studies, 38 , 39 which reported longer ratio of follow-up increases the chances of developing virological failure. Our finding indicated participants who had low CD4 counts had higher chance of virological failure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Machine learning predictive algorithms have the potential to improve the quality of care and predict the needs of HIV patients by analyzing huge amounts of data, and enhancing prediction capabilities [ 42 , 43 ]. Furthermore, machine learning is used to identify HIV patients who are at high risk of failing to adhere and being a virological failure [ 44 ] and able to learn from domain experts quickly and accurately, then apply that knowledge to identify HIV risk behaviors in a huge dataset [ 45 ]. Ethiopia has a severe HIV pandemic with increasing virological failure [ 46 ].…”
Section: Introductionmentioning
confidence: 99%